Nursing Comiittee to Coping with COVID-19 in Bahia - Tatiane Araújo-; Handerson Silva Santos; Mariana de Almeida Moraes; Fernanda Carneiro Mussi
ABSTRACT Objective: To report the experience of the Nursing Committee for Coping with COVID-19 in Bahia. Methods: The experience report describes motivation, objectives, representatives, organization, working groups, activities and impact of the Committee actions. Results: The Committee consists of educational institutions and class representation. It accepts demands, questions and complaints from nursing workers, acts in favor of safe care and inspection of health and safety conditions at work. Five working groups and six technical support groups were formed. These groups address Communication, Review of Health Services Contingency Plans, Assistance to Long-Term Institutions, Epidemiology and External Activities. An Instagram account was created for quick and reliable access to information, and also an email to meet demands and monitor COVID-19 cases. Conclusion: The results of the Committee work contribute to guide, support, value and defend nursing workers in coping with COVID-19